Appendiceal malakoplakia masquerading as a cecal mass. Issue 5 (1st June 2020) - Musonza, Tashinga; Tschen, Jose Antonio
Abstract: Appendiceal malakoplakia masquerading as a cecal mass is uniquely rare. The presence of an infiltrate of granular eosinophilic macrophages containing Michaelis–Gutmann bodies on histopathology is pathognomonic of malakoplakia. Cutaneous, gastrointestinal and most commonly urogenital malakoplakia is reported in association with an immunocompromised state, infectious, inflammatory and neoplastic processes. Presentation varies from microscopic disease to plaques, nodules, polypoid lesions and small masses. However, a cecal mass postea proven appendiceal malakoplakia deserves special attention. We could not find similar case reports in the English literature. The pathogenesis of malakoplakia is poorly understood, and it is unclear if it is a harbinger of malignancy, a precursor lesion or an inflammatory marker. In the setting of a dominant appendiceal mass, post-treatment endoscopic and tumor marker surveillance is paramount but, however, undefined in contemporary literature.